Alcohol use among adolescents: prevalence, risk factors and prevention strategy in a rural area in the Brazilian state of Pará (Research, Society and Development, 2020)
The use of psychotropic drugs, such as alcohol, is one of the factors that limit healthy development, both in the physical and psychosocial spheres of adolescents. In northern Brazil, the epidemiological scenario on alcohol use is still poorly known, especially in rural areas. Thus, this study determined prevalence and factors associated with alcohol use among adolescents in the rural area of the municipality of Bragança (Pará), as well as identified a prevention strategy to be used in the school environment. This cross-sectional study consisted of information related to alcohol use, school performance and demographic and socioeconomic characteristics of adolescent students from public schools in rural communities in the municipality of Bragança, Pará. Logistic regression models identified factors associated with alcohol use in life and in the last 30 days. The prevalence of alcohol use at least once in life and in the last 30 days was 35.7% and 17.6%, respectively. Male gender, school failure, no or little parental participation in school life, low mother's education, parents using any psychotropic drugs, friends using any psychotropic drugs, all or most friends using psychotropic drugs, and involvement in conflicts were associated with alcohol use. Informal talks and conversations were the two prevention strategies most recommended by adolescents. In summary, these rates of alcohol use in rural area are similar to those recorded in the urban area of Pará and indicate the need for actions to promote the health of adolescents.